Impact of cavotricuspid isthmus depth on the ablation index for successful first-pass typical atrial flutter ablation - Manabu Kashiwagi (Nature Portfolio, 2021)
Abstract Cavotricuspid isthmus (CTI) linear ablation has been established as the treatment for typical atrial flutter. Recently, ablation index (AI) has emerged as a novel marker for estimating ablation lesions. We investigated the relationship between CTI depth and ablation parameters on the procedural results of typical atrial flutter ablation. A total of 107 patients who underwent CTI ablation were retrospectively enrolled in this study. All patients underwent computed tomography before catheter ablation. From the receiver-operating curve, the best cut-off value of CTI depth was < 4.1 mm to predict first-pass success. Although the average AI was not different between deep CTI (DC; CTI depth ≥ 4.1) and shallow CTI (SC; CTI depth < 4.1), DC required a longer ablation time and showed a lower first-pass success rate (p < 0.01). In addition, the catheter inversion technique was more frequently required in the DC (p < 0.01). The lowest AI sites of the first-pass CTI line were determined in both the ventricular (2/3 segment of CTI) and inferior vena cava (IVC, 1/3 segment of CTI) sides. The best cut-off values of the weakest AIs at the ventricular and IVC sides for predicting first-pass success were > 420 and > 386, respectively. Among patients with these cut-off values, the first-pass success rate was 89% in the SC and 50% in the DC (p < 0.01). Although ablation parameters were not significantly different, the first-pass success rate was lower in the DC than in the SC. Further investigation might be required for better outcomes in deep CTIs.